Infant with diffuse large B-cell lymphoma identified postmortem with homozygous founder Slavic RAG1 variant: a case report and literature review - Volodashchik, Tatiana P.; Polyakova, Ekaterina A.; Mikhaleuskaya, Taisia M.; Sakovich, Inga S.; Kupchinskaya, Aleksandra N.; Dubrouski, Aliaxandr Ch.; Belevtsev, Mikhail V.; Dasso, Joseph F.; Varabyou, Dzmitry S.; Notarangelo, Luigi D.; Walter, Jolan E.; Sharapova, Svetlana O. (Frontiers in Pediatrics, 2024)
There is an increased risk of lymphomas in inborn errors of immunity (IEI), however, germline genetic testing is rarely used in oncological patients, even those with early-onset of cancer. Our study focuses on a child with recombination activating gene 1 (RAG1) deficiency who was identified through a screening program for Slavic founder genetic variants among patients who died with malignancy at an early age in Belarus.Results: We identified one homozygous founder RAG1 variant out of 24 available DNA samples from 71 patients who developed lymphoma <3 years of age from Belarusian cancer registry from 1986 to 2023. Our patient had an episode of pneumonia at 3 months of age and was hospitalized for respiratory distress, candida-positive lung disease and lymphadenopathy at 14 months of age. The diagnosis of Epstein-Barr virus (EBV)+, diffuse large B-cell lymphoma (DLBCL) was established. The patient had a normal lymphocyte count that decreased over time.One month after chemotherapy initiation, the patient died due to sepsis and multiple organ failure without a genetic diagnosis. In a retrospective analysis, T cell receptor excision circles (TRECs) and kappa-deleting recombination excision circles (KRECs) were undetectable in peripheral blood.A targeted screening program designed to detect a Slavic founder variant in the RAG1 gene among children revealed a 14 month-old Belarusian male with low TREC levels who died of EBV-driven DLBCL and complications of chemotherapy including infections. This case highlights how IEI can initially present with non-infectious complications, such as malignancy. This case highlights how patients with IEI and recurrent infections may develop serious non-infectious complications, such as fatal malignancy. It also emphasizes the importance of early identification, such as newborn screening for severe combined immune deficiency (SCID).Earlier diagnosis of RAG deficiency could have prompted hematopoietic stem cell transplant well before the DLBCL occurrence. This likely would impact the onset and/or management strategies for the cancer.